2013
DOI: 10.1016/j.jcjo.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Use of microperimetry to evaluate hydroxychloroquine and chloroquine retinal toxicity

Abstract: Objective: To check the ability of microperimetry to detect early retinal damage in rheumatic patients taking hydroxychloroquine (HCQ) and/or chloroquine (CQ). To describe the microperimetric alterations attributable to these drugs and their correlation with some clinical variables. Results: Significant differences in microperimetry indexes were detected between cases and controls, between patients of different age groups, and between patients taking CQ and HCQ. Significant differences were also detected in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 18 publications
0
33
1
3
Order By: Relevance
“…These results were contradictory to the results of two studies [7,8] that were conducted in 2013 and used microperimetry as a novel screening test for retinal toxicity caused by antimalarial drugs. Both studies concluded that microperimetry, though not being a recommended test of screening, could provide important information regarding visual function in patients on HCQ therapy [7,8].…”
contrasting
confidence: 76%
See 1 more Smart Citation
“…These results were contradictory to the results of two studies [7,8] that were conducted in 2013 and used microperimetry as a novel screening test for retinal toxicity caused by antimalarial drugs. Both studies concluded that microperimetry, though not being a recommended test of screening, could provide important information regarding visual function in patients on HCQ therapy [7,8].…”
contrasting
confidence: 76%
“…Both studies concluded that microperimetry, though not being a recommended test of screening, could provide important information regarding visual function in patients on HCQ therapy [7,8].…”
mentioning
confidence: 99%
“…Es un dato difícil de analizar de manera aislada. Es muy dependiente del factor aprendizaje por lo que el resultado puede no ser fiable 67 .…”
Section: El Tercer íNdice Es Macular Integrity O Integridad Macular (unclassified
“…Nosotros encontramos a 3 pacientes con depósitos corneales de los cuales 2 presentaban maculopatía 67 .…”
Section: Discusión Fase I Estudio Con Microperimetríaunclassified
See 1 more Smart Citation